Managerial leadership and teacher performance: a systematic review of principal effectiveness in elementary education - Muchtar Rizki Ramadhani; Garianto Garianto; Agus Sutanto (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study aims to identify and synthesize evidence from previous studies on factors influencing the principal's role in improving teacher performance, and to develop a conceptual framework derived from various findings. This research employs the Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Searches were conducted across five databases (Scopus, Web of Science, ERIC, Google Scholar, and SINTA). From 457 initial articles, only 100 passed the screening and were analyzed using thematic synthesis. From the 100 articles, four main factors influencing principal leadership on teacher performance were identified: 1) principal internal factors (managerial competence, leadership style, communication, and charisma); 2) school environmental factors (school culture, organizational climate, and academic supervision); 3) teacher factors (work motivation, commitment, discipline, and pedagogical competence); and 4) system and policy factors (compensation, professional development, community-based policies, and school committee roles). Among these four factors, principals' managerial competence was the most dominant (mentioned in 78 of 100 articles). Additionally, teacher work motivation was found to play an important mediating role, mentioned in 65 of 100 articles. Sustainable improvement in teacher performance can be achieved through strengthening principals' managerial competence, enhancing teacher motivation and commitment, developing positive school culture and climate, and reinforcing supervision and supportive policies. These findings are expected to serve as a reference framework for education stakeholders and a foundation for future researchers to conduct field testing.